A strategy for evaluating micro-doppler signature and motion parameter of ship over time-varying sea surface. Issue 10 (19th May 2022) - Shi, Fang-Yuan; Li, Jin-Xing; Liu, Gu; Wang, Liu-Ying; Zhang, Min
ABSTRACT: The micro-Doppler ( m -D) signature can describe the motion state and structure of the target in detail. It can be considered as an effective method for ship target detection and recognition in the marine environment. In this paper, an effective strategy is proposed to simulate the m-D signature and extract the ship's motion parameters on the time-varying sea surface. For this purpose, a ship target micro-motion model based on six degrees of freedom is first established. Then, the public domain strip (PDSTRIP) method is used to realize real-time estimation of ship motion. Next, a high-precision electromagnetic scattering model is used to generate radar echoes of a ship on the rough sea. Finally, the m-D signature can be acquired and analysed based on the obtained radar echo. The numerical results show that the instantaneous frequency and motion parameters can be estimated well from the m-D signature. At the same time, the proposed model can also be used to calibrate the Inverse Synthetic Aperture Radar (ISAR) of ship targets in the marine environment.